An Assessment of the Expertise Required of Workers, in the Context of Their Capacity to Cope With Libya’s Fourth Industrial Revolution - E Mohamad; H.T Saeid Balrwein; M.A A Rahman; N.A. A., Nor Azlan; M.S Abd Rahman; A Saptari (JIE Scientific Journal on Research and Application of Industrial System, 2020)
The advent, of Libya‘s fourth industrial revolution (4IR), rendered the structure of the country‘s smart factories exceedingly intricate, vibrant and variable. Several investigators, in this domain, believe that the most significant factors, influencing the outcome of Libya‘s 4IR, are the skills gap and manpower development issues. In order for the 4IR to progress, it is crucial that more sophisticated capabilities be developed. This undertaking should begin with an assessment of the existing expertise of the stakeholders themselves (self-evaluation). The purpose of this exercise, is to identify the deficiency in skills, with regards to the skill sets, that are essential for the 4IR. This calls an evaluation of the stakeholders‘ degree of comprehension regarding the 4IR, and their willingness to involve themselves in this exercise. Stakeholders both within and beyond Libya‘s manufacturing division, should be taken into account for this evaluation. The main objective, of this study, is to ascertain the impact of 4IR, on the aspects of human labour and work organization. To achieve this objective, we opted for the quantitative method. A questionnaire was formulated to scrutinize every single detail in the manpower‘s supply chain, stretching from Libya‘s learning system to its workforce.